Indole-3-Carbinol (I3C) and its Major Derivatives: Their Pharmacokinetics and Important Roles in Hepatic Protection - Wang, Si-qi; Cheng, Li-sha; Liu, Yun; Wang, Ji-yao; Jiang, Wei (Current Drug Metabolism, 2016)
Background: Indoles, including indole-3-carbinol (I3C) and its derivatives, are the products of glucosinolate hydrolysis catalyzed by the enzyme myrosinase. Under acidic conditions, I3C polymerizes into 3, 3- diindolylmethane (DIM), [2-(indol-3-ylmethyl)-indol-3-yl]indol-3-ylmethane (LTr1), 1-(3-hydroxymethyl)- indolyl-3-indolylmethane (HI-IM) and indolo[3,2b]carbazole (ICZ). Recently, I3C and its dimer DIM have shown pleiotropic protective effects on chronic liver injuries, including viral hepatitis, hepatic steatosis, hepatic cirrhosis, hepatocellular carcinoma, and so on. Methods: We reviewed the published papers about the pharmacokinetics of I3C and its derivatives in vitro and in vivo, and summarized their multiple protective roles in the processes of chronic liver diseases. Results: Indoles not only regulate transcriptional factors and their respective signaling pathways, but also relieve oxidative stress and inhibit the synthesis of DNA to influence the activation, proliferation and apoptosis of target cells. Moreover, indoles modulate the enzymes that are relevant to hepatitis viral replication, lipogenesis, and the metabolism of ethanol and some hepatotoxic substances to protect the liver. Currently, the immunomodulatory biofunction of indoles contributes to improving non-alcoholic steatohepatitis. In addition, indoles also function as the inhibitors of pro-inflammatory cytokines and chemokines to reduce microbial-induced liver injures. Conclusion: Indoles, especially I3C and DIM as phytochemicals, exert anti-fibrosis, anti-tumor, anti-oxidant, immunomodulatory, detoxification and anti-inflammation effects on hepatic protection through pleiotropic mechanism.
Keywords: 3' -diindolylmethane (DIM)